After the Astana declaration: is comprehensive primary health care set for success this time?. Issue 6 (12th November 2019) - Kraef, Christian; Kallestrup, Per
Abstract : Primary health care (PHC) strengthening in order to achieve the Sustainable Development Goal has again, 40 years after the Alma-Ata declaration, been declared a priority by the global health community. Despite initial progress the Alma-Ata vision of Health for All by the year 2000 was not realised. In this analysis we (1) examine the challenges that comprehensive PHC faced after the Alma-Ata declaration, (2) provide an analysis of the current opportunities and threats to comprehensive PHC strengthening on the global, national and community level and (3) review the most important policy recommendations and related evidence to address these threats for success of the Astana declaration. Factors that are predominantly opportunities are the treasure of historical lessons from the past 40 years, the increased attention to social and environmental determinants of health, the global economic growth and new technologies, in particular digital medicine, which also have the potential to revolutionise community involvement. Factors that are currently predominantly threats are insecurity, conflicts and disease outbreaks; lack of sustained political commitment and inappropriate monitoring and evaluation structures; inappropriate and unsustainable financing models; insufficient health workforce recruitment, employment and retention; missing support of physicians and their professional organisations; inadequately addressing the needs of the community and not giving attention to gender equity. In contrast to the policy and evidence context in 1978 when Alma-Ata was passed there are today policy recommendations and a large body of evidence that can address the threats to comprehensive PHC—and turn them into opportunities.